PTH-129 Evaluation of simulation-based induction programme to enhance acquisition of handling skills for upper GI endoscopy. (8th June 2018) - Edwards, Kate; Siau, Keith; Neville, Peter; Turner, Jeff; Beale, Amanda; Green, Susi; Murugananthan, A; Hawkes, Neil
Abstract : Introduction: Endoscopic training pathways in the UK need to support efficient development of complex motor skills. Previous studies have demonstrated benefit from use of simulators in the early phase of training. However a target of a 25% improvement performance should be demonstrated to remain cost effective. The SPRINT induction programme aims to provide a structured sequence of training elements to optimise and accelerate the early phase of training in upper GI endoscopy. We hosted a Tri-deanery simulation training event using the Surgical Science EndoSIM. Methods: Baseline data on previous training experience was obtained from 20 trainees attending the SPRINT induction. Pre-course self-assessed competency scores in 12 upper GI handling skills domains were provided and mapped to the Joint Advisory Group on GI Endoscopy (JAG) DOPS assessment forms. Domain scores were given a rating from 0–10 on a Likert scale (0=not at all competent, 10=very competent). Trainees completed a structured curriculum of simulator training and a series of small group teaching seminars on technical aspects of endoscopy and lesion recognition. At the end of the course trainees provided further self-assessed competency scores and rating scores for small group teaching sessions. Differences in the competency scores were determined by the Mann Whitney U test with an alpha value of 0.01. The proportion of trainees with less (0–25 procedures) and more experience (26–50 procedures) reporting greater than 25% domain score change was tested using the Chi-squared statistic. Results: Paired scores (n=20) showed a significant increase across all 12 upper GI handling skills domains following the training intervention (p<0.01, alpha=0.01, two-tailed). The proportion of trainees reporting >25% difference in domain scores was greater for trainees with less experience compared to more experienced trainees [p<0.05 for all domains]. All trainees rated good/excellent small group sessions in scope handling, lesion recognition, and endoscopic non-technical skills. Conclusion: This study demonstrates significant benefit from the EndoSIM simulator across all upper GI technical skills domains. Simulation training is best targeted in the early stages of endoscopy training (0–25 cases), but there remains some benefit to more experienced trainees. Small group training provides additional value during the SPRINT induction. These findings further support inclusion of simulation as part of the JAG certification pathway for upper GI endoscopy.